Pulmonary artery penetration due to fish bone ingestion: A rare case report - Ho Xuan Tuan, MD, PhD; Nguyen Duy Hung, MD, PhD; Nguyen Nhat Quang, MD; Nguyen-Thi Tam, MD; Nguyen-Thi Hai Anh, MD; Tran Hoa, MD, PhD; Bui The Dung, MD, PhD; Nguyen Minh Duc, MD (Radiology Case Reports, 2024)
Accidental fish bone ingestion is a common manifestation at emergency departments. In most cases, ingested foreign bodies usually pass uneventfully through the gastrointestinal tract and complications only present in less than 5% of all patients. In this report, we present the first documented case of pulmonary artery injury due to a fish bone in a 63-year-old male patient hospitalized with hemoptysis after accidentally swallowing a fish bone 30 days ago. This patient subsequently had surgery and endoscopy to safely remove the foreign body and then recovered well on a follow-up examination. For cases of fish bone ingestion, contrast-enhanced chest computed tomography is one of the most essential tools to assess vascular problems and associated mediastinal infections-risk factors for life-threatening and long-term recurrent inflammation. Reconstructing planes along the foreign body axis and changing windows when analyzing CT scans is necessary to avoid missing lesions and dilemmas.